Acerca de los conceptos de política y soberanía en Carl Schmitt y Thomas Hobbes - Marcos, Dolores (Foro Interno, 2004)
This article provides a discussion of the concepts of politics, sovereignty and man in the thinking of CARL SCHMITT and THOMAS HOBBES, clarifying certain similarities and differences between the two authors. It attempts to understand the well-known theory of the German author concerning that which is political, as drawn from the struggle and distinction between friend/foe in light of the threat posed by the Hobbesian state of nature and the meaning of war. These ideas call for a State that does not arise as the result of a contract, but from unity based on exclusions, according to SCHMITT. The Acerca de los conceptos de política Dolores Marcos y soberanía en Carl Schmitt y Thomas Hobbes need for an absolute power that can protect and coerce connects with certain features of HOBBES´ Leviathan. Finally, the conflictive dimension of man is understood as essential for the political realm, which is based, precisely, on egotistical and dange rous features in human beings. Understanding this sphere turns out to be essential for developing an approach to the resolution of conflicts.